PENGARUH PDB SEKTOR PERTANIAN, NILAI TUKAR PETANI DAN INVESTASI SEKTOR PERTANIAN TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PERTANIAN DI INDONESIA - ERLINA; Iskandar Iskandar (Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to determine the effect of agricultural sector GDP, farmer exchange rates and agricultural sector investment on employment absorption in Indonesia simultaneously or partially in 2010-2020. This study uses time series data with multiple linear regression analysis using the E-Views version 12 application which produces a variable coefficient value of GDP in the agricultural sector – 0.155395 and has no significant effect on employment in the agricultural sector. The coefficient value of the farmers exchange rate is 16010.90 and has a significant effect on the absorption of labor in the agricultural sector. The investment coefficient value is -113.2570 and has no significant effect on employment in the agricultural sector. The coefficient of determination (R2) is 0.6154 or 61.54%. While the remaining 38.46% is influenced by other factors not examined in this study.